PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) PADA MATA PELAJARAN SEJARAH MATERI KERAJAAN - KERAJAAN ISLAM DI INDONESIA - Yona Liza; Liza Husnita; Juliandry Kurniawan Junaidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the tendency of history learning to rely on conventional teaching methods that provide limited opportunities for students to participate actively in the learning process. Therefore, the Teams Games Tournament (TGT) learning model was selected as an alternative instructional strategy to create a more active, engaging, and enjoyable learning environment through the Open The Box educational game supported by Wordwall. This study employed a descriptive qualitative approach. Data were collected through observation, interviews, documentation, and triangulation. The research participants consisted of a history teacher and students of Class X E6. The implementation of the learning model involved lesson planning, teacher presentation of learning materials, group formation, presentation of the Open The Box game by the teacher, students' participation in the tournament, and the provision of group rewards. The findings indicate that the implementation of the Teams Games Tournament (TGT) model using the Open The Box game successfully encouraged students to participate actively in classroom activities, express their opinions confidently, answer questions, and collaboratively discuss challenges presented in the game. However, several challenges were identified, including the presence of students who remained passive and had difficulty maintaining focus, indicating the need for more effective classroom time management and group organization. Overall, the integration of the Teams Games Tournament model with the Open The Box educational game successfully created an interactive, engaging, and enjoyable learning environment that effectively supported the achievement of history learning objectives.